To solve the given linear-quadratic system using the substitution method, we have the equations:
- \( y = x^2 - 4x - 41 \) (quadratic equation)
- \( y = 4 \) (linear equation)
We will substitute the value of \( y \) from the second equation into the first equation.
Step 1: Substitute \( y = 4 \) into the quadratic equation
Substituting \( y = 4 \) into \( y = x^2 - 4x - 41 \):
\[ 4 = x^2 - 4x - 41 \]
Step 2: Rearrange the equation
Rearranging the equation gives:
\[ x^2 - 4x - 41 - 4 = 0 \] \[ x^2 - 4x - 45 = 0 \]
Step 3: Factor or use the quadratic formula
We need to solve the quadratic equation \( x^2 - 4x - 45 = 0 \). We can factor it:
\[ (x - 9)(x + 5) = 0 \]
Step 4: Set each factor to zero
Setting each factor equal to zero gives us:
\[ x - 9 = 0 \quad \Rightarrow \quad x = 9 \]
\[ x + 5 = 0 \quad \Rightarrow \quad x = -5 \]
Step 5: Find corresponding \( y \) values
Now we substitute \( x = 9 \) and \( x = -5 \) back into the linear equation \( y = 4 \):
- For \( x = 9 \):
\[ y = 4 \]
- For \( x = -5 \):
\[ y = 4 \]
Step 6: Write the solutions
Thus, the solutions to the linear-quadratic system are:
- \( (9, 4) \)
- \( (-5, 4) \)
These are the points where the quadratic graph intersects the line \( y = 4 \).